Dataset describing Aotearoa New Zealand young adults’ psychological well-being and behaviour during nationwide lockdown - Broodryk, Terise; Robinson, Kealagh (Data in brief, 2022)
This dataset provides a comprehensive snapshot of 277 New Zealand young adult's (M age = 18.93, SD = 3.28) real-time behaviours and experiences during a seven-week nationwide lockdown. Participants were recruited through a university student participant pool and data were collected online during 20–27th April 2020 (Alert Level 4) and 6–13th May 2020 (Alert Level 3), constituting the 26th–33rd and 42nd–49th day (respectively) of a nationwide lockdown to manage the first wave of COVID-19 in Aotearoa New Zealand. Data have been used previously [1]. Data includes participants’ self-reported compliance with legally mandated COVID-19 lockdown policies, as well as participants’ self-reported knowledge of lockdown policies, lockdown characteristics, trust in government and information sources, COVID-19 specific worries, recent anxiety, depression, and stress symptoms, cognitive reappraisal and expressive suppression use, and Big Five personality traits. The dataset is freely accessible (CC-BY-4.0 license) at https://osf.io/pa4n3/. This database can provide insight into the psychological experience of strict COVID-19 lockdown, support policy makers to evaluate the efficiency COVID-19 public health messaging, and inform future policy to support public health and wellbeing during widespread lockdown and quarantine.